412 Clinico-pathological features and treatment particularities of incidentally diagnosed endometrial adenocarcinoma in infertile women. (18th September 2019) - Kaabia, O; Aymen, L; Nourallah, G; Rym, Z; Aymen, S; Mohamed, B; Hédi, K
Abstract : Objectives: The aim of this study was to investigate the clinical and prognostic features of women under 45 with the incidental diagnosis of endometrial adenocarcinoma (EC) during infertility work-up, with special attention given to treatment approaches and survival rates. Methods: The medical records of 228 patients who were diagnosed with EC at our center between 2008 and 2018 were included in the study and analysed retrospectively. Out of these patients, 9.6% (n=22) were ≤ 45 years. Eleven patients had a history of infertility and had been diagnosed with EC during a hysteroscopic evaluation for infertility. We compared these patients to the other eleven patients diagnosed with EC under 45 with no infertility history. Results: The mean age at diagnosis was comparable in both groups (39.8 ± 6.7 vs 39.7 ± 5.5 years, p=0.98). The mean duration of infertility was 5.4 ± 2.1 years. The Body mass Index was high in both groups (33.0 ± 5.4 vs 30.3 ± 4.5 years, p=0.48). There were no significant difference in terms of early stage cancer (p=0.79). Fertility sparing treatment was initiated in 9 patients but after 6 months only 3 had a complete pathological response. There was no difference in OS and DFS between the 2 groups (respectively, p=0.97 et p=0.48). Conclusions: The investigation of the endometrium during infertility work-up may lead to the diagnosis of asymptomatic EC that does not seem to have any specific prognostic features even though it may allow a fertility sparing treatment.